The effect of leadership and work environment On Work Motivation and Implications Performance of Dinas Pengairan of Eemployees Purwodadi Grobogan - Supriyadi, Supriyadi (-)
The purpose of this research is to know the influence of leadership and work environment  on motivation and  performance employees of  Dinas Pengairan, Grobogan. This study is a survey. The data is primary data taken by sampling method, as many as 52 respondents. Data analyzed with validity and reliability test, partial test ( t test ), simultaneously test ( F test ), R-square and path analysis. T test result shows that : leadership is significant positive effect on work motivation, work environment is significant positive effect on the work motivation, leadership is significant positive effect on the performance, work environment  is significant positive effect on the performance, work motivation is significant effect on the performance. F test result shows that simultaneously leadership, work environment, and motivation has significant positive effect on the performance.  R-square test result shows that  87.55% variation of performance can be explained by leadership, work environment, motivation and the remaining 12.45% is explained by other factors out of the model. The path analysis show : the direct effect of  leadership on performance variables is greater than the indirect effect of leadership on performamce by mediating motivation, the direct effect of  work environment  on performance variables is greater than the indirect effect of work environment  on performamce by mediating motivation. Based on a total leverage to improve performance will be more effective if through increased work environment. Keywords : leadership,  work environment, work motivation, performance